Carbon dioxide reforming of methane over promoted NixMg1−xO (111) platelet catalyst derived from solvothermal synthesis - Yu, Mingjue; Zhu, Kake; Liu, Zhicheng; Xiao, Haipeng; Deng, Wei; Zhou, Xinggui (Applied catalysis. B, Environmental, 2014)
•A facile solvothermal and topotactic transformation route to generate M-NixMg1−xO (111) platelet (M=Sn, Ce, Mn or Co) catalyst is established.•Mn- and Ce-segregate as separate phase and do not enhance the coke-resistant performance of NixMg1−xO (111) platelet catalyst.•Co- and Sn-promoted NixMg1−xO (111) platelet catalysts inhibit Cβ formation in CH4-CO2 dry reforming reaction, as they are uniformly distributed on the catalyst.•Co does not passivate Ni activity and displays superior coke-resistance properties under harsh reaction conditions. A bottom-up approach is developed to synthesize Sn, Ce, Mn, or Co promoted NixMg1−xO catalysts enclosed by Tasker III type polar (111) facets. Sn and Co are evenly distributed on NixMg1−xO, whereas Ce and Mn segregate as separate oxides. X-ray diffraction (XRD), N2 physisorption, X-ray photoelectron spectroscopy (XPS), and Transmission Electron Microscopic (TEM) measurements are carried out to understand the structure/composition of both fresh and spent catalysts. H2-Temperature Programmed Hydrogenation (TPH), XPS and Thermogravimetric analysis (TG) are employed to elucidate the types of coke formed on the spent catalysts. Mn does not show obvious enhancement to catalytic stability towards Cβ formation, and a lower activity is observed as it separates from catalyst surface and causes agglomeration of NixMg1−xO(111) platelets. Cβ and whisker carbons are found for Ce-promoted NixMg1−xO(111) catalyst, for Ce segregates as CeO2. Both Sn and Co are distinguished to enhance the coke-resistant properties of NixMg1−xO catalyst in CH4-CO2 dry reforming, as they inhibit the formation of Cβ. Activation energy (Ea) measurements show that Sn lowers the activity of Ni surfaces, while Co does not passivate the intrinsic activity of Ni surfaces. Under more critical reaction conditions with CH4/CO2 ratio of 3 and diluent gas free, Co is found to enhance the lifespan of NixMg1−xO (111) catalyst.